Methodology and Evaluation of Large Deformations in Romanesque Pillars (Global Journals of Research in Engineering, 2022)
There is a set of Romanesque churches at Val d#x2019;Aran that were built between the eleventh and thirteenth centuries. One of the main features of these buildings is the presence of large deformations masonry as in the church of Santa Maria d#x2019;Arties (XII) in which arches and vaults have funicular shapes. The assessment is based on a three-dimensional model obtained with a terrestrial laser scanner (TLS). Geometrical evaluation of the least rigid elements, the pillars, allows to analyze the displacements. It is not only possible to deduce the regression plane of the central-nave pillars#x2019; displacements but also to define the deformation vectors over it. The methodology of this study focuses on the assessment of the deformations they have suffered. The point cloud is processed with the software Cyclone, the program 3DReshaper (2016) and, finally, with Google SketchUp (2019).
Keywords: romanesque; barrel vaults; masonry pillars; great deformations; val d#x2019; aran